P–665 Influence of premature progesterone elevation on embryo development. (6th August 2021) - Lefebvre, T; Duval, G; Loubersac, S; Lammers, J; Barriere, P; Freour, T; Reignier, A
Abstract: Study question: Does a serum progesterone level higher than 1.3 ng/mL on the day of ovulation trigger have an impact on blastocyst development? Summary answer: Elevated progesterone level has no significant impact on top blastocyst rate, usable blastocyst rate and on morphokinetics. What is known already: Premature elevation of progesterone level on the day of ovulation trigger prior to IVF is common and causes a decrease in endometrial receptivity. A freeze all strategy is then recommended. However, cumulative live birth rates have also been described as lower in cases of high progesterone levels. Study design, size, duration: This was a retrospective bicentric cohort follow-up study, including 1150 IVF/ICSI cycles performed between 2016 and 2018 with at least 1 day–5 blastocyst available for transfer or freezing. Among these cycles, 524 were performed with use of a time-lapse system (Embryoscope). Serum Progesterone level was measured on the day of ovulation trigger, and a value >1.3 ng/ml was used to identify premature progesterone elevation. Participants/materials, setting, methods: The cycles were divided into 2 groups according to serum progesterone level: 1335 cycles were allocated in the normal progesterone group (P < 1, 3) and 215 in the progesterone premature elevation group (P > 1.3). Patient's characteristics, ovarian stimulation characteristics, IVF cycles characteristics and embryology parameters were anonymously recorded and compared between the 2 groups. Main results and the role of chance: Female age, smoking status, AFC and AMH levels were comparable between the 2 groups. Female BMI was significantly higher in the P < 1, 3 than in the P > 1.3 group (26.1 versus 24.7 kg/m² respectively). Total FSH dose, estradiol level, number of follicles >11mm and number of retrieved oocytes were significantly higher in the P > 1.3 group than in P < 1.3 group No difference was observed between the 2 groups in terms of top blastocyst rate per mature oocyte and usable blastocyst rate per mature oocyte. When morphokinetic analysis was available, time to blastulation was the only significantly different parameter between the 2 groups (110.4 hours in P < 1.3 versus 107.9 hours in P > 1.3, p = 0.04). Cumulative live birth rate per cycle was not statistically different between the two groups (23.1% for P < 1.3 versus 28.7% for P > 1.3) (p > 0.05). Limitations, reasons for caution: The retrospective design of the study should lead to careful analysis of the results. The progesterone threshold refers to a specific assay, and should not be generalized to other assays. Wider implications of the findings: Premature elevation of serum progesterone level on the day of ovulation trigger does not seem to affect embryo developmental competence. This further supports the relevance of freeze all strategy in this situation. Trial registration number: Not applicable